Report of a novel KIR3DS1*0130104 allele discovered using advanced molecular techniques - Yindom, L; Wang, L; Okala, S; Dong, T; Rowland-Jones, S (2014)
KIR3DS1*0130104 is identical to KIR3DS1*0130101 except for changes at positions 1768 (C>T) and 12617 (C>A). © 2014 John Wiley and Sons A/S.